Europe's regions within the currency Union: Risks and opportunities - Ian Robins (Spatial implications of the European Monetary Union, 2004)
In this paper the differences that the single currency might make to the regions of countries within the euro-zone are considered. It is still too early for much evidence to be available about the effects of EMU. Therefore the discussion is concerned mainly with what theoretical considerations would lead us to expect. Some empirical observations illustrate the expectations. Chief drawbacks of the euro are seen in the possible inappropriateness of interest rates, the absence of fiscal and related adjustment measures, the relative immobility of labour and the restrictions on national governments with relation to regional policies. Principal advantages lie in the stimulus that the drawbacks give to rethinking regional policy and fostering patterns of industrial diversity in which more flexible labour markets are encouraged.
hdl:10419/59967; http://econpapers.repec.org/RePEc:zbw:arlssd:6
Keywords: 330